Shakespeare, idealism, and universals: the significance of recent work on the mind - Gabriel Egan (2011)
For most the twentieth century, the serious study of Shakespeare's works was founded on a general acceptance of the principles of Platonic idealism and essentialism, and a belief in the existence of universals. In textual criticism, the New Bibliography that emerged from the work of A. J. Pollard, W. W. Greg, and R. B. McKerrow in the first decades of the century assumed a relatively unproblematic application of Platonic idealism for the relationship between the play as conceived in the mind of the dramatist and the play as performed or written down. Since the 1980s idealism, essentialism, and universals have become dirty words as the New Historicism and Cultural Materialism popularized an unthinking association between these philosophical principles and political conservatism. In these new and related schools, the alleged antidote to all three evils was said to be materialism, which meant paying more attention to the physical (often the economic) realities of a system under consideration than to the ideas in it. In respect of the textual condition of Shakespeare's plays, this meant attending to the material particularities of the early quarto and Folio texts rather than seeking to extrapolate back from those to a lost authorial manuscript that preceded them or, worse still, to whatever it is Shakespeare had 'in mind' when he composed them.